Análise do impacto das fusões e aquisições na criação de valor e no retorno das ações ordinárias dos principais bancos brasileiros de grande porte entre 2003 e 2013 - Bertoncelo, Valeria Regina (2015)
Mergers and acquisitions (M&As) represent the possibility of creating shareholder value. The decisions for such investment size have different motivations, many justified on economic theories: the maximization of firm´s profits and management utility. The measurement of results of transactions with M&As, in short and long terms, was by the event study method and the Economic Value Added - EVA®, respectively. The industry segment analysis was financial institutions, especially banks with shares traded on the BOVESPA and total assets in excess of R$500 million. The specificity and the preponderance of financial institutions in the Brazilian economy reveal that 22 transactions of Mergers and Acqusitions (M&As) from the year 2003 to 2013 did not achieve, in the short term, cumulative abnormal returns that is statistically significant; on the other hand, the long-term performance, measured by EVA® in most of the studied cases, created shareholder value®.